Sistem Pengendalian Internal dalam Akuntabilitas Laporan Keuangan Pemerintah - Sigit Sugiarto (Insan Cita Bongaya Research Journal, 2024)
This study aims to determine the influence of the government's internal control system on the accountability of the South Sulawesi government's financial statements. The data collection technique uses primary data obtained from questionnaires. The population in this study is all auditors who work at the South Sulawesi Inspectorate Office. The sampling technique in this study uses a saturated sampling technique so that the number of samples is 49 respondents. The data analysis method uses a simple linear regression analysis method. The results of the study show that the Government Internal Control System has a positive and significant effect on the Accountability of Government Financial Statements